Kajian Pendugaan Erosi pada Kawasan Terasering Panyaweuyan Kecamatan Argapura Kabupaten Majalengka - Shalih Abrar Fayruzi; Hilwati (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Argapura District is one of the rural areas located in the eastern part of Majalengka Regency which has various potentials to be developed. Judging from the morphological conditions, the Argapura sub-district is a highland village located just below the foot of Mount Ciremai. Meanwhile, judging from the accessibility of its location, Argapura District is a rural area with low accessibility, even some villages tend to be isolated. Argapura District has several tourist attractions, one of which is the Panyaweuyan Terrace Area, in the form of an area planted with vegetable crops on land that has a steep slope. The purpose of this study is to identify the Panyaweuyan Terrace Area as an area that provides protection for its subordinate areas, and to estimate the magnitude of erosion that occurs in Panyaweuyan hills which are planted with vegetables. The analytical model used is land suitability analysis for protected forest areas and erosion estimation analysis. Protected forest areas include areas that provide protection for their subordinate areas, so that if damage occurs in this area, it will affect the subordinate area. If there is erosion in this area, the consequences will also be experienced by the area below it. Abstrak. Kecamatan Argapura merupakan salah satu wilayah perdesaan yang terletak di bagian timur Kabupaten Majalengka yang memiliki beragam potensi untuk dikembangkan. Dilihat dari kondisi morfologinya wilayah Kecamatan Argapura merupakan perdesaan dataran tinggi yang berada tepat di bawah kaki Gunung Ciremai. Sedangkan dilihat dari aksesibilitas lokasinya Kecamatan Argapura merupakan perdesaan dengan aksesibilitas rendah bahkan beberapa desa cenderung mengarah ke terisolasi. Kecamatan Argapura mempunyai beberapa objek wisata, salah satunya adalah Kawasan Terasering Panyaweuyan, berupa kawasan yang ditanami tanaman pertanian sayuran pada lahan yang mempunyai kemiringan curam. Tujuan studi ini adalah mengidentifikasi Kawasan Terasering Panyaweuyan sebagai kawasan yang memberikan perlindungan kawasan bawahannya, dan menduga besarnya erosi yang terjadi di bukit Panyaweuyan yang ditanami dengan sayuran. Model analisis yang digunakan adalah analisis kesesuaian lahan kawasan hutan lindung dan analisis pendugaan erosi. Kawasan hutan lindung termasuk kawasan yang memberikan perlindungan kawasan bawahannya, sehingga jika terjadi kerusakan di kawasan ini akan berpengaruh terhadap kawasan bawahannya. Jika terjadi erosi di kawasan ini, maka akibatnya akan dialami juga oleh kawasan yang ada di bawahnya